Nonsteroidal anti-inflammatory drugs versus placebo for post-endoscopic retrograde cholangiopancreatography pancreatitis: a systematic review and meta-analysis - Serrano, Juan Pablo Román; de Moura, Diogo Turiani Hourneaux; Bernardo, Wanderley Marques; Ribeiro, Igor Braga; Franzini, Tomazo Prince; de Moura, Eduardo Turiani Hourneaux; Brunaldi, Vitor Ottoboni; Salesse, Marianne Torrezan; Sakai, Paulo; De Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2019)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) is the primary therapeutic procedure for treatment of diseases that affect the biliary tree and pancreatic duct. While the therapeutic success rate of ERCP is high, the procedure can cause complications, such as acute pancreatitis (PEP), bleeding, and perforation. This meta-analysis aimed to assess the efficacy of nonsteroidal anti-inflammatory drugs (NSAIDs) in preventing PEP following (ERCP).Materials and methods We searched databases, such as MEDLINE, Embase, and Cochrane Central Library. Only randomized controlled trials (RCTs) that compared the efficacy of NSAIDs and placebo for the prevention of PEP were included. Outcomes assessed included incidence of PEP, severity of pancreatitis, route of administration, and type of NSAIDs.Results Twenty-one RCTs were considered eligible with a total of 6854 patients analyzed. Overall, 3427 patients used NSAIDs before ERCP and 3427 did not use the drugs (control group). In the end, 250 cases of acute pancreatitis post-ERCP were diagnosed in the NSAIDs group and 407 cases in the placebo group. Risk for PEP was lower in the NSAID group (risk difference (RD): −0.05; 95 % confidence interval (CI): −0.07 to – 0.03; number need to treat (NNT), 20; P < 0.05). Use of NSAIDs effectively prevented mild pancreatitis compared with use of placebo (2.5 % vs. 4.1 %; 95 % CI, −0.05 to – 0.01; NNT, 33; P < 0.05), but the information on moderate and severe PEP could not be completely elucidated. Only rectal administration reduced incidence of PEP (6.8 % vs. 13 %; 95 % CI, −0.10 to – 0.04; NNT, 20; P < 0.05). Furthermore, only diclofenac or indomethacin use was effective in preventing PEP.Conclusions Rectal administration of diclofenac and indomethacin significantly reduced risk of developing mild PEP. Further RCTs are needed to compare efficacy between NSAID administration pathways in prevention of PEP after ERCP.